2017
DOI: 10.1111/ijfs.13437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synergistic and antagonistic effects between some selected antioxidants by means of an electrochemical technique

Abstract: Summary This work presents a systematic study of the possible interactions in mixtures of the natural antioxidants eugenol, thymol, sesamol and limonene. The antioxidant capacity is measured from the decrease of the DPV signal corresponding to the H2O2 oxidation on a mercury electrode in the presence of the antioxidants. A three‐level full factorial design was used to analyse the antioxidant capacity of forty five mixtures. The higher synergistic effect was reached in the mixtures containing eugenol and sesamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Palma et al. found that the intermediate free radicals generated during carvacrol oxidation increased free radical formation, making ROS production markedly more efficient during Hg/H 2 O 2 oxidation [34]. Furthermore, as indicated by the antibacterial experiment, KGM‐P exhibited a satisfactory antibacterial effect when applied to fresh muffins (Figure 3), effectively inhibiting microbial growth and slowing the lipid oxidation process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Palma et al. found that the intermediate free radicals generated during carvacrol oxidation increased free radical formation, making ROS production markedly more efficient during Hg/H 2 O 2 oxidation [34]. Furthermore, as indicated by the antibacterial experiment, KGM‐P exhibited a satisfactory antibacterial effect when applied to fresh muffins (Figure 3), effectively inhibiting microbial growth and slowing the lipid oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the blank group, the KGM‐P group exhibited a lighter appearance but no visible mould. This difference could be attributed to the inhibitory effect on lipid oxidation provided by the KGM‐P film [34]. In summary, the muffins packaged in KGM‐P films maintained an appropriate specific volume and showed a satisfactory appearance with a significant improvement in colour and hardness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of reactions increases as many compounds are present in a sample and with the number of matrices combined, since this raises the amplitude of interactions [ 32 ]. Furthermore, two compounds that interact in one way in a reaction environment can exhibit other behaviors when exposed to another mixture with different constituents [ 33 ]. An antagonism occurs when two or more compounds react, and the result is lower than the mathematical sum of the individual effects [ 32 ].…”
Section: Resultsmentioning
confidence: 99%